Apresentação | Foreword | Présentation | Presentazione - Magliacane, Alessia; Rubino, Francesco; Pontes, José Antonio Siqueira (DESC - Direito, Economia e Sociedade Contemporânea, 2020)
Editorial DESC, v. 2, n. 2 (2019)